PROMOTING "CERDIK" BEHAVIOR AND IMPROVING DIETARY HABITS TO REDUCE HYPERTENSION IN ELDERLY - Prastia, Tika Noor; Syari, Wirda; Anggraini, Sevrima; Alfiana, Ramdan; Sintani, Rapika Dea; Nurlani, Inne; Dahliawati, Anis; Alfiani, Risa Ramisah; Azizah, Nita Ratu (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Non-communicable diseases (NCDs) represent the predominant cause of mortality on a global scale, contributing to 73% of deaths within Indonesia, with 26% of these fatalities occurring among adults. Hypertension ranked as the third most prevalent cause of death following stroke and tuberculosis, continues to pose a substantial public health challenge within the Indonesian context. Within the jurisdiction of Pancasan Community Health Center, it is identified as one of the regions exhibiting the highest prevalence of hypertension, with 53 documented cases. This community service initiative was designed to tackle hypertension through health education interventions specifically aimed at the residents of RW 09, Pasir Jaya Urban Village. The program concentrated on advocating for the "CERDIK" behavioral model and enhancing the dietary practices of individuals in Pasir Jaya Urban Village suffering from hypertension. By employing pre-test and post-test questionnaires, the efficacy of health education disseminated via presentations and video materials was meticulously assessed. The findings indicated a notable enhancement in awareness regarding the prevention and management of hypertension. This intervention was effective in cultivating awareness and facilitating behavioral modifications essential for preventing non-communicable diseases, thereby improving public health outcomes, particularly among the elderly demographic.